Examining the Role of Social Media in Shaping Undergraduate Students' Study Preferences - Halim, Fransiscus Ati; Nandini, Gusti Ketut Siska Sri; Lumbantoruan, Nova Indah (ULTIMA InfoSys, 2025)
Abstract – Social media has become an essential aspect of daily life, particularly for students who rely on these platforms to access information related to their educational assignments and course materials. Driven by this trend, the author conducted a study using a quantitative approach and survey research to explore how students' interest in learning is influenced by their use of social media. The study focused on students from the UMN Information Systems Study Program, Class of 2022, examining two main variables: the independent variable, social media use, and the dependent variable, students' interest in learning. Various statistical tests were applied to analyze the relationship between these variables, including normality, residual, and correlation analyses. The results indicated heteroscedasticity in the residuals of the social media and interest variables; however, no autocorrelation was observed between the residuals of variables such as social media and interest, interest and time, and interest and productivity. Keywords - Interest in Learning, social media, educational assignment, Normality Analysis